2017
DOI: 10.1080/07434618.2017.1332685
|View full text |Cite
|
Sign up to set email alerts
|

The availability and accessibility of basic concept vocabulary in AAC software: a preliminary study

Abstract: Core vocabulary lists obtained through the analyses of children's utterances include a variety of basic concept words. Supporting young children who use augmentative and alternative communication (AAC) to develop their understanding and use of basic concepts is an area of practice that has important ramifications for successful communication in a classroom environment. This study examined the availability of basic concept words across eight frequently used, commercially available AAC language systems, iPad© ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…In addition, teachers must include vocabulary on the AAC device that meets the unique needs of the individual child (i.e., fringe words), keeping in mind that the language needs of each student in the classroom may be different (Bean et al, 2019). When selecting the individualized vocabulary, teachers should consider words that align with classroom academic topics, terms commonly used by the teacher, typical vocabulary for classroom peers (i.e., age level, grade level), and descriptive words used to describe location and time (McCarthy et al, 2017).…”
Section: Set Up the Systemmentioning
confidence: 99%
“…In addition, teachers must include vocabulary on the AAC device that meets the unique needs of the individual child (i.e., fringe words), keeping in mind that the language needs of each student in the classroom may be different (Bean et al, 2019). When selecting the individualized vocabulary, teachers should consider words that align with classroom academic topics, terms commonly used by the teacher, typical vocabulary for classroom peers (i.e., age level, grade level), and descriptive words used to describe location and time (McCarthy et al, 2017).…”
Section: Set Up the Systemmentioning
confidence: 99%
“…For example, an AAC system used in school setting will need academic concept representation. McCarthy et al (2017) showed that many age-appropriate concept words were not adequately represented or easily accessible in four commercially available AAC systems. The authors highlighted the need for educators to recognize and address the limitations of basic concept content in pre-packaged AAC software or applications.…”
Section: Introductionmentioning
confidence: 99%
“…).L'accès au vocabulaire de base est un outil puissant pour que les utilisateurs de CAA atteignent une communication fonctionnelle, notamment dans l'environnement scolaire(McCarthy et al 2017). Dès lors, la prise en compte du vocabulaire de base dans le domaine de la CAA est primordiale.…”
unclassified